Frog Virtual Learning Environment for Malaysian schools: exploring teachers’ experience - Cheok, Mei Lick; Wong, Su Luan (Springer, 2016)
This paper is a case study exploring 12 school teachers’ experiences in using FROG VLE in their teaching and learning. FROG VLE is a learning management system which the Malaysian government has adopted for all its 10,000 government aided schools nationwide. This ambitious programme which connects all the schools within a single online platform though has caused the country a substantial amount of money, has not been reciprocated with the same amount of enthusiasm by its teachers. A report published by its Auditor-General (2013) revealed poor usage in schools. This study interviewed 12 teachers in order to understand the workings in schools that had caused the poor usage of the VLE. All teachers, despite coming from different states and schools, seemed to resonate in terms of the challenges and limitations faced. No one denies the benefits and strength of the e-learning approach for the betterment of the education system. This paper elaborates and highlights these teachers’ concerns and frustrations, and recommendations for better implementation reform are included.